2001
DOI: 10.4049/jimmunol.167.1.283
|View full text |Cite
|
Sign up to set email alerts
|

IL-1 Induced Chemokine Production Through the Association of Syk with TNF Receptor-Associated Factor-6 in Nasal Fibroblast Lines

Abstract: The fibroblasts stimulated by cytokines released the chemokine and recruited the infiltrating cells, including eosinophils, that play a key role in the pathogenesis of airway disease. We established the human fibroblast lines showing high Syk expression and the lines showing low Syk expression from pieces of nasal polyp. IL-1 induces the interaction of TNFR-associated factor (TRAF) 6 with IL-1R-associated kinase, which is rapidly recruited to the IL-1R after IL-1 induction, whereas TRAF2 participates in TNF-α-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
40
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 36 publications
2
40
1
Order By: Relevance
“…All these results confirm the essential role of chemokines in chemoattraction and cell guidance to the site of infection during bacterial infection. IL1 has been reported to activate chemokine production [45]. In our study, we found that IL1 was moderately up-regulated after 24 hours of stimulation and that it occupies a central position in the LPS-related network 2 providing a global image of inflammation activation (Figure 4B).…”
Section: Discussionmentioning
confidence: 51%
“…All these results confirm the essential role of chemokines in chemoattraction and cell guidance to the site of infection during bacterial infection. IL1 has been reported to activate chemokine production [45]. In our study, we found that IL1 was moderately up-regulated after 24 hours of stimulation and that it occupies a central position in the LPS-related network 2 providing a global image of inflammation activation (Figure 4B).…”
Section: Discussionmentioning
confidence: 51%
“…In addition to these signaling cascades, much evidence has been accumulating that Syk also play a critical role in some parts of integrin signaling in neutrophils and macrophages (Vines et al, 2001;Mocsai et al, 2002). Furthermore, an essential role of Syk in IL-1-induced RANTES (regulated on activation normal T cell expressed and secreted) production in human nasal fibroblasts was suggested by an antisense experiment (Yamada et al, 2001). These data increase the value of Syk kinase inhibitor as a broad anti-inflammatory agent.…”
Section: Discussionmentioning
confidence: 68%
“…Although many factors are considered to be angiogenic, VEGF, IL-8, and HGF are all exceptionally important and powerful inducers of angiogenesis for solid tumors and are constitutively or inductively secreted from tumor cells and/or mesenchymal stromal cells (26 -31). The stromal fibroblasts are induced to secrete HGF and VEGF by the stimulation of IL-1, basic fibroblast growth factor, and platelet-derived growth factor derived from tumor cells and macrophages in the tumor tissue (32)(33)(34)(35)(36).…”
Section: Discussionmentioning
confidence: 99%